2023
DOI: 10.1038/s41467-023-37683-7
|View full text |Cite
|
Sign up to set email alerts
|

Piezo2 regulates colonic mechanical sensitivity in a sex specific manner in mice

Abstract: The mechanosensitive ion channel Piezo2 in mucosa and primary afferents transduces colonic mechanical sensation. Here we show that chemogenetic activation or nociceptor-targeted deletion of Piezo2 is sufficient to regulate colonic mechanical sensitivity in a sex dependent manner. Clozapine N-oxide-induced activation of Piezo2;hM3Dq-expressing sensory neurons evokes colonic hypersensitivity in male mice, and causes dyspnea in female mice likely due to effects on lung sensory neurons. Activation of Piezo2-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…S3E,F). These observations suggest the antibodies used in this study show reasonable specificity, in agreement with previous confirmation reported [50][51][52][53][54][55][56][57] , while also confirming the detection of message for both Piezo1 and Piezo2 in the RPE/choroid tissue above.…”
Section: Detection In Rpe Cells and Validation Of Antibody Specificitysupporting
confidence: 92%
See 1 more Smart Citation
“…S3E,F). These observations suggest the antibodies used in this study show reasonable specificity, in agreement with previous confirmation reported [50][51][52][53][54][55][56][57] , while also confirming the detection of message for both Piezo1 and Piezo2 in the RPE/choroid tissue above.…”
Section: Detection In Rpe Cells and Validation Of Antibody Specificitysupporting
confidence: 92%
“…Additional support from others validates the staining of the antibodies used in this study, including KO mice models, reporter mice, pre-absorption assay, or genetically modified cell lines [50][51][52][53][54][55][56][57] .…”
Section: Strengths Of the Study And Comparison To Othersmentioning
confidence: 62%
“…Piezo2, a vital mechanosensitive ion channel for proprioception, touch, and bladder stretch sensation, is widely expressed in sensory neurons, indicating its critical physiological role during mechanical sensitization [43,44]. Based on our knowledge, it's the rst report regarding the upregulation of Piezo2 in TG neurons in TMJOA chronic pain rats.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the role of Piezo1 in direct ENS mechanotransduction should be interpreted cautiously. By comparison, many studies highlight the robust mechanosensitive role of Piezo2 in ENS [ 137 , 138 , 139 ]. We speculate the difference in mechanotransduction between Piezo1 and Piezo2 originates from the kinetics differences despite their similar structure.…”
Section: Piezo1 Affects the Biological Function Of The Digestive Systemmentioning
confidence: 99%